2023
DOI: 10.1007/s11845-023-03493-5
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy-assisted prevalence of hair loss after COVID-19 vaccination among an Egyptian population: a cross-sectional study

Amr M. Ammar,
Ibrahim S. Ibrahim,
Abbas N. Mohamed
et al.

Abstract: Abstact Background Coronavirus disease (COVID-19) currently named SARS-CoV-2 is a contagious disease caused by a coronavirus; incompatible data are present on the possible relationship among COVID-19 vaccines and hair loss. Aims The objective of the current study was to assess dermoscopically the prevalence of hair loss among an Egyptian population following COVID-19 vaccination. Methods A total of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Moreover, perifollicular inflammation manifested by the accumulation of activated macrophages and mast cell degranulation in the context of psychological stress as well as the ischemia and vascular decompensation caused by the hypercoagulability state and microthrombus formation were described as major culprits in inducing hair loss [ 18 ]. Moreover, a recent study reported an increased incidence of hair shedding following COVID-19 vaccinations [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, perifollicular inflammation manifested by the accumulation of activated macrophages and mast cell degranulation in the context of psychological stress as well as the ischemia and vascular decompensation caused by the hypercoagulability state and microthrombus formation were described as major culprits in inducing hair loss [ 18 ]. Moreover, a recent study reported an increased incidence of hair shedding following COVID-19 vaccinations [ 19 ].…”
Section: Discussionmentioning
confidence: 99%